Effect of Organic Nano-NPK Formulation on Fruit Yield and Quality in Banana Cv. Nendran (Musa AAB) - Deepa, H. L.; Reshmi, C. R.; Rafeekher, M.; Aparna, B. (International Journal of Bio-resource and Stress Management, 2022)
The present study was carried out in the Department of Fruit Science, College of Agriculture, Vellayani, Thiruvananthapuram, Kerala, India during October, 2020 to November, 2021 to evaluate the effect of soil application of organic Nano-NPK formulation on fruit yield and quality in banana cv. Nendran. The earliest bunch emergence (164.62 days) was noticed in T7 (soil test-based KAU POP recommendation) and it was on par with T6 (45 g Nano-NPK in 6 splits). Application of 45 g Nano-NPK in 6 splits (T6) resulted in the highest number of hands bunch-1 (4.84), maximum values for length of finger (23.59 cm), girth of finger (13.26 cm), pulp-peel ratio (3.55) and total biomass yield. T6 and T7 significantly improved the bunch weight, number of fingers bunch-1, number of fingers in D hand and weight of fingers. T6 recorded the highest values for total sugars (19.94%), reducing sugars (15.17%), total carotenoids (303.67 mg 100 g-1), sugar-acid ratio (63.92), ascorbic acid content (2.2%) and moisture content (24.95%). T6 recorded the highest peel thickness (3.06 mm), which was on par with T7. T6 (45 g Nano-NPK in 6 splits) also recorded the longest shelf life (10.15 days) and the fruits took longer time for ripening (6.32 days). The study revealed that the application of 45 g granular organic Nano-NPK in 6 splits along with 10 kg FYM and 100 g lime plant-1 year-1 increased the overall growth, yield and quality of banana cv. Nendran with high net income and B:C ratio.